2021
DOI: 10.1111/1751-2980.13025
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the rate of recurrence of postoperative Crohn's disease with biological therapy. A meta‐analysis

Abstract: Objective Preventing the postoperative recurrence (POR) of Crohn's disease (CD) poses a significant challenge to clinicians. With the advent of biologics, various studies have observed a reduction of recurrence after surgery. Hence, we performed a systematic review and meta‐analysis to identify the rate of POR at different time points in the era of biologic use. Methods We performed a literature search using Medline and Embase databases for studies investigating biologics in preventing the POR of CD. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
(68 reference statements)
0
4
1
Order By: Relevance
“…Histopathological predictors did not reach statistical significance in our analysis, in contrast to the findings observed in previous studies [20][21][22][23]34]. However, in the univariate analysis, the presence of granulomas and transmural inflammation at the margin of resection showed numerical differences between the POR and recurrence-free groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Histopathological predictors did not reach statistical significance in our analysis, in contrast to the findings observed in previous studies [20][21][22][23]34]. However, in the univariate analysis, the presence of granulomas and transmural inflammation at the margin of resection showed numerical differences between the POR and recurrence-free groups.…”
Section: Discussioncontrasting
confidence: 99%
“…More importantly, in the context of early postoperative immunomodulators (EPI), whether treatment initiation (either sustained or initiated) has been a matter of controversy [32,33]. A recent meta-analysis showed that the timing of initiating biologic therapy (BT) after surgery does not have a significant impact on POR [34]. Therefore, further clarification is needed to determine whether EPI is effective in preventing POR when compared to an introduction of these therapies after endoscopic recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ten patients treated with infliximab, two (20%) had endoscopic POR compared to one (10%) in the group of ten adalimumab patients (a non-statistically significant difference, although the sample size of the study may be relatively small to assess statistical significance). Finally, several meta-analyses (including some network meta-analyses) have confirmed similar efficacy of both anti-TNF agents for the prevention of POR [ 12 , 101 , 106 108 ].…”
Section: Anti-tnf Agentsmentioning
confidence: 99%
“…Compared with infliximab, this network meta-analysis yielded the following results on the effect on endoscopic POR: adalimumab (OR, 0.92; 95% CI, 0.18–4.75), thiopurines (OR, 4.11; 95% CI, 0.68–24.8), placebo (OR, 4.39; 95% CI, 0.70–3.68), and mesalamine (OR, 37.8; 95% CI, 3.77–379.4) On the basis of a network meta–analysis combining direct and indirect evidence either adalimumab or infliximab may be used in the postoperative prophylaxis of CD POR 2019 Erős [ 107 ] Anti-TNF agents were significantly better in preventing clinical, endoscopic, severe endoscopic and histological POR compared to conventional therapies (OR, 0.508; 95% CI, 0.309–0.834; OR, 0.312; 95% CI, 0.199–0.380; OR, 0.195; 95% CI, 0.107–0.356; and OR, 0.255; 95% CI, 0.106–0.611, respectively). Infliximab and adalimumab proved to be equally effective Anti-TNF agents are more effective in preventing clinical, endoscopic, and histological POR than conventional therapies 2021 Jain [ 108 ] Twenty-four studies were included in the meta-analysis. The endoscopic, clinical, and surgical POR rates with the use of anti-TNF agents at one year were 21.7% (95% CI, 16.3–28.4%), 13.1% (95% CI, 8.2–18.9%) and 3.8% (95% CI, 1.4–9.9%), respectively.…”
Section: Anti-tnf Agentsmentioning
confidence: 99%
“…In recent years, several meta-analyses have been published evaluating the efficacy of anti-TNF agents in preventing postoperative clinical and endoscopic recurrence, mostly showing a greater efficacy on both outcomes compared to therapies such as mesalazine and AZA [ 105 , 106 , 107 ]. Beelen et al conducted a meta-analysis of individual participant data from six RCTs, reporting that anti-TNF were superior to thiopurines in preventing endoscopic (RR 0.52, 95% CI 0.33–0.80) and clinical POR (RR 0.50; 95% CI, 0.26–0.96) as well as severe endoscopic recurrence (RR 0.41; 95% CI, 0.21–0.79), confirming the superiority of anti-TNF in preventing both endoscopic and clinical POR after ICR.…”
Section: Prophylaxis Of Postoperative Recurrencementioning
confidence: 99%